(untitled) (مجلة إحالات, 2026)
The poet is a creation of his environment, an expression thataccompanied the evolution of literary criticism movement since ancient times. This notion emphasizes on the important impact of the environment on the poetic composition, considering pandemics as one of its environmental effects. Thus, it is incumbent upon literature, including poetry, to represent it, based on the emotions it leaves behind, which are difficult to overcome. The poets are inclined to evoke many artistic images to depict the duality of pain and hope through their lexical choices, structural techniques, and rhetorical expressions. This is appears in many contemporary poetic experiences that sought to provide a vivid portrayal of what the pandemic, particularly COVID-19 and its impacts on individuals and society at large, undermining the globalized village that it strived to build, turning them into isolated communities preoccupied with their own affairs. Notably, on the poetic level, the feminist poem relies on artistic images that intersect with those available in male poetry. Therefore, this research paper aims to elucidate these artistic images between the two experiences concerning nature, gender, and impact, relying on the tools of comparative study.